Serological Typing of 31 Achromogenic and 40 Melanogenic Pseudomonas aeruginosa Strains - Yabuuchi, Eiko (1971)
Thirty-one achromogenic and 40 melanogenic Pseudomonas aeruginosa strains were studied with 10 monovalent typing sera (3). Twenty-one of the achromogenic (67.7%) and seven of the melanogenic (17.5%) strains were agglutinated by one of the 10 typing sera. Ten achromogenic and 33 melanogenic strains were not agglutinated by any of the 10 typing sera. As far as this set of antisera is concerned, the typability of achromogenic and melanogenic P. aeruginosa strains appears to be much lower than that of the chromogenic, nonmelanogenic strains of the species reported previously.